THE USE OF RUSSIAN PASSIVE VOICE STRUCTURE FROM THE POINT OF VIEW OF VIETNAMESE PEOPLE (Journal of Foreign Language Studies, 2024)
Giới thiệu luận án tiến sĩ "Cách sử dụng cấu trúc bị động tiếng Nga theo quan điểm của người Việt (Употребление русских пассивных конструкций с позиции носителя вьетнамского языка)".